Mycobacterium avium subsp. paratuberculosis (MAP) infection in the endangered huemul deer (Hippocamelus bisulcus) in Patagonia - Corti, Paulo; Collado, Bernardita; Riquelme, Carlos; Tomckowiack, Camilo; Salgado, Miguel (Austral Journal of Veterinary Sciences, 2020)
In a huemul (Hippocamelus bisulcus) population sympatric with cattle, we found evidence of Mycobacterium avium subsp. paratuberculosis (MAP) infection. Three huemul faecal pellet samples and two cows pats were collected and cultured for MAP presence. DNA was then extracted for PCR analysis of all signal-positive cultures. To assess whether MAP isolates obtained from huemul faeces were associated with typical MAP isolated from livestock, positive confirmed culture samples were sub-typed using a combination of five Mycobacterial Interspersed Repetitive Unit-Variable Number Tandem Repeat Analysis and one Short Sequence Repeat analysis markers. All faecal samples from both species were MAP positive. One huemul presented a different bacteria profile genotype not described before, suggesting that huemul and cattle in Patagonia could carry a unique MAP strain.